Unstable Power Threatens the Powerful and Challenges the Powerless: Evidence from Cardiovascular Markers of Motivation - Daan eScheepers; Charlotte eRöell; Naomi eEllemers (Frontiers in Psychology, 2015)
Possessing social power has psychological and biological benefits. For example, during task interactions, people high in power are more likely to display a benign cardiovascular response pattern indicative of challenge whereas people low in power are more likely to display a maladaptive cardiovascular pattern indicative of threat (Scheepers, De Wit, Ellemers, & Sassenberg, 2012). Challenge is marked by high cardiac output (CO) and low total peripheral resistance, while threat is marked by low CO and high TPR (Blascovich & Mendes, 2010). In the current work we addressed a possible moderator of the power-threat/challenge relationship, namely the stability of power. We examined the influence of the stability of power (roles could or could not change) on cardiovascular responses during a dyadic task where one person was the chief designer (high power) and one person was the assistant (low power). During the task, different cardiovascular-measures were taken (CO, TPR, Heart Rate [HR], Pre-Ejection Period [PEP]). Whereas participants in the unstable low power condition showed a stronger tendency towards challenge, participants in the unstable high power condition showed a stronger tendency towards threat. Moreover, participants in the stable low power condition showed cardiovascular signs of task disengagement. Results are discussed in terms of the importance of contextual variables in shaping the relationship between power and benign/maladaptive physiological responses.